Development and Prediction of Context-Dependent Vowel Pronunciation in Elementary Readers. (2nd January 2019) - Steacy, Laura M.; Compton, Donald L.; Petscher, Yaacov; Elliott, James D.; Smith, Kathryn; Rueckl, Jay G.; Sawi, Oliver; Frost, Stephen J.; Pugh, Kenneth R.
ABSTRACT: As children learn to read, they become sensitive to context-dependent vowel pronunciations in words, considered a form of statistical learning. The work of Treiman and colleagues demonstrated that readers' vowel pronunciations depend on the consonantal context in which the vowel occurs and reading experience. Using explanatory item-response models we examined child- and nonword-factors associated with children's assignment of more versus less frequent grapheme-phoneme correspondences (GPC) to vowel pronunciations as a function of rime coda in monosyllabic nonwords. Students ( N = 96) in grades 2-5 read nonwords in which more versus less frequent vowel GPCs were wholly supported or partially favored by the rime unit. Use of less frequent vowel GPCs was predicted by set for variability, word reading, and rime support for the context-dependent vowel pronunciation. We interpret the results within a developmental word reading model in which initially incomplete and oversimplified GPC representations become more context dependent with reading experience.